Gerakan Plastic Exchange Melalui Pemanfaatan Ecobrick di Desa Bendelan Bondowoso - Ni Luh Ayu Sukmawati; Audy Putri Lestari; Alifiyah Haafizhoh; Dinda Yulia Saputri; Andini Femy Pramudya; Dian Faqih Kurniawan; M.Aghis Azria Al Fathonian (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The problem of plastic waste in Indonesia has become an increasingly urgent issue to be addressed. One of the areas facing serious waste management challenges is Bendelan Village in Binakal District, Bondowoso Regency. The lack of waste processing facilities and community awareness are key factors exacerbating the situation. Through a community service program, efforts were made to introduce and utilize ecobricks as a solution for managing plastic waste. This program involved PKK cadres in the socialization and creation of ecobricks. The outcome of this program was the creation of 20 ecobrick bottles, reflecting active community participation in the Plastic Exchange movement. This initiative is expected to be sustainable and contribute positively to creating a cleaner and healthier environment.